A Comparison of Forward and Futures Prices of an Interest Rate‐Sensitive Financial Asset - MEULBROEK, LISA (Journal of Finance, 1992)
ABSTRACT This paper focuses on contractual distinctions as an explanation for the price divergence between futures and forward contracts. Specifically, it investigates the effect of marking‐to‐market on the observed price differences using the pricing model described in Cox, Ingersoll, and Ross (CIR) (1981, Journal of Financial Economics 9 , 321–346). Using previously unavailable data, this paper employs Eurodollars, an interest rate‐sensitive financial asset, to test the CIR model. Unlike prior empirical studies, test results support both the weak prediction concerning the sign of the average price difference and the stronger prediction that specific covariances explain the variation in the price differences.